JBE. CONCEPT AND APPLICATION - Mitkovets, Lydia; Sidorov, Daniel; Gourinovitch, Alevtina (PROFESSIONAL STUDIES: Theory And Practice, 2022)
To save the information inside storage users try to reduce the files size to minimum by using data compression software. It is a new algorithm for data compression in this article. It is jbit encoding (JBE). This algorithm manipulates each bit of data inside file to minimize the size without losing any data after decoding. It is classified lossless compression. This basic algorithm is combining with other data compression algorithms to optimize the compression ratio. The implementation of this algorithm consists in a combination of various data compression algorithms. Keywords: compression, encoding, source encoding.